A NOVEL METHODOLOGY FOR GEOVISUALIZING EPIDEMIOLOGICAL DATA - Guerroudji Meddah, Fatiha (University of Eloued جامعة الوادي, 2022)
Rapid advances in geographic information systems (GIS) and related technologies have created a potential for dynamic geovisualization methods to be integrated with GIS in support of a range of decision-making tasks. Cartographic visualization is then considered as an extension of spatial analysis, and GIS is configured as a spatial decision support system. This integration can add a great deal to epidemiologic research and is essential for health policy planning, decision making, and ongoing surveillance efforts. In this context, this paper presents a novel methodology to support interactive visual exploration and analysis of epidemiological data by coupling MapInfo GIS software with the Gastner area cartogram, a particular class of map type where some aspect of the geometry of the map is modified to accommodate the studied problem. The aim of the study is to help improve public health by identifying areas of exposure and risk on tuberculosis in the city of Oran in Algeria
Forum Intervention of Artificial Intelligence and Its Applications. Faculty of Exat science. University of Eloued
Keywords: GIS, Geovisualization, Cartograms, Tuberculosis, Epidemiology